2017
DOI: 10.1165/rcmb.2016-0191oc
|View full text |Cite
|
Sign up to set email alerts
|

Roflumilast N-Oxide in Combination with Formoterol Enhances the Antiinflammatory Effect of Dexamethasone in Airway Smooth Muscle Cells

Abstract: Roflumilast is an orally active phosphodiesterase 4 (PDE4) inhibitor approved for use in chronic obstructive pulmonary disease. Roflumilast N-oxide (RNO) is the active metabolite of roflumilast and has demonstrated anti-inflammatory impact in vivo and in vitro. To date, the effect of RNO on the synthetic function of airway smooth muscle (ASM) cells is unknown. We address this herein and investigate the effect of RNO on β2-adrenoceptor-mediated, cAMPdependent responses in ASM cells in vitro, and whether RNO enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…MKP-1upregulation is a common response to elevated cAMP induced by a diverse range of stimuli. In ASM cells we have shown that inflammatory stimuli [134], cAMP elevating agents [133], as well as respiratory medicines such as β2-agonists [133,135] and phosphodiesterase 4 inhibitors [136,137], can all increase MKP-1 via CREB-mediated pathways and perhaps offset the impact of cAMP on cytokine production. In 2016, we used selective antagonists of EP2 (PF-04418948) and EP4 receptors (GW 627368X) to show that PGE2…”
Section: Airway Inflammationmentioning
confidence: 99%
“…MKP-1upregulation is a common response to elevated cAMP induced by a diverse range of stimuli. In ASM cells we have shown that inflammatory stimuli [134], cAMP elevating agents [133], as well as respiratory medicines such as β2-agonists [133,135] and phosphodiesterase 4 inhibitors [136,137], can all increase MKP-1 via CREB-mediated pathways and perhaps offset the impact of cAMP on cytokine production. In 2016, we used selective antagonists of EP2 (PF-04418948) and EP4 receptors (GW 627368X) to show that PGE2…”
Section: Airway Inflammationmentioning
confidence: 99%
“…It has been known for some time that β2-agonists have beneficial effects beyond bronchodilation and that they exert antiinflammatory actions in a cAMP-dependent manner [5]. We have shown that this beneficial impact is due in part to the upregulation of MKP-1; that is, in ASM cells, cAMP-elevating agents (including β2-agonists) can also increase expression of anti-inflammatory molecules (MKP-1) to repress inflammation [6][7][8][9]. But what is the effect of cAMP-elevating agents on TTP in ASM cells?…”
Section: Introductionmentioning
confidence: 82%
“…Secondly, we investigated receptor-mediated pathways and induced production of cAMP as a secondary messenger by activation of Gs-coupled protein receptors (β2-adrenergic receptors and EP2/EP4 prostanoid receptors) with cognate ligands β2-agonists and prostaglandin E2 (PGE2), respectively. In all cases, MKP-1 was used as a positive control as it well-established as being upregulated by cAMP [6][7][8][9]15]. Finally, we investigated the underlying signaling pathways involved.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro study has shown that roflumilast N-oxide in combination with formoterol significantly enhanced the effect of dexamethasone in ASM (19). It potentiated formoterol-induced expression of mitogen-activated protein kinase phosphatase 1 (MKP-1).…”
Section: Asm Cellsmentioning
confidence: 99%